Evaluating The Effectiveness of Physical and Economic Management Strategies on the Sustainability of Tourist Attractions in Ol Pejeta Conservancy, Laikipia County, Kenya - Mwangi, Lucy Wanjiru; Fwaya, Erick; Miriti, Gilbert (Journal of Tourism Sustainability, 2025)
Sustainability is an essential strategic concept for tourist attractions. However, the current rise in visitor numbers globally threatens this concept. This calls not only for the need to implement relevant visitor management strategies to oversee these numbers but also to ensure that the adopted strategies effectively facilitate proper visitor behaviour. Ol Pejeta Conservancy, Kenya, is a key tourist attraction that upholds sustainability as its strategic concept. However, the rise in visitor numbers over the past five years threatens the sustainability aspects of the site. Hence, using this site as a case study, this paper aims to assess the effectiveness of two major visitor management strategies - physical and economic - on the sustainability of tourist attractions. The study initially targeted 227 visitors, from whom 167 completed and returned the questionnaires. The collected data were analysed statistically using multiple linear regression. Results reveal that physical and economic management strategies play a crucial role in ensuring the sustainability of tourist attractions. Thus, they offer actionable insights to tourism managers in similar settings to implement effective strategies for sustainable efforts in tourist attractions.